If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 4y = 7y + -1 Combine like terms: 4y + 4y = 8y 8y = 7y + -1 Reorder the terms: 8y = -1 + 7y Solving 8y = -1 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 8y + -7y = -1 + 7y + -7y Combine like terms: 8y + -7y = 1y 1y = -1 + 7y + -7y Combine like terms: 7y + -7y = 0 1y = -1 + 0 1y = -1 Divide each side by '1'. y = -1 Simplifying y = -1
| 5(x+10)=40 | | 5(x-4)=3x-7 | | 36.90=9 | | x-3=-27 | | 9p-7p+4p-6p= | | 3x/4=9/2 | | 9y^2+54y+0=0 | | 9x+8=4x-3 | | -3=-27 | | -2(2x-4)+8x-4= | | -12=-3/4z | | 17q-14xq=11q | | 3x(t-3)=27 | | x/-11=5 | | F=9/5x+32 | | 9x-(2x-1)=37 | | 36/(2x)=6 | | 5+x=-22 | | 5(7b-6)=110 | | -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 | | -1.3+2.7=.2y | | -13x+22=37 | | 7/3a=14 | | y=-9x+44 | | 3x(12-3)=27 | | 6x+19=8x+7 | | -2(5x-6)-12=-2(9s+4)-3 | | b+b2+b/6=190 | | 4*x^3+5*x^2+x=1 | | -10m-4=4-10m | | (4+8x)/(2x+1) |